History of pharmacy according to Zbigniew Bela (in Polish) - Anita Magowska (Studia Historiae Scientiarum, 2018)
This article focuses on life and scientific developments of Zbigniew Bela (1948–2018) who was professor of the history of pharmacy and director of the Museum of Pharmacy of Jagiellonian University in Cracow. The aim of the article is to identify specificity of his research activity, particular because he was a Polish language scholar, however, interested in the history of pharmacy. It was proven that he used literary perspective to investigate the history of pharmacy that was very original and peculiar. His most important achievements were monographs inspired and illustrated by items from the Museum of Pharmacy in Cracow, especially the 16th century formulary by Alexey from Piedmont.